PEMBUATAN GAME EDUKASI BERBASIS KINECT UNTUK ANAK BERKEBUTUHAN KHUSUS (AUTIS) BERTEMA LINGKUNGAN RUMAH - Yosima, Febrilia Putri; , Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Abstract Children with special needs autism is a brain disorder which affects the mental development of the children that usually makes the children having some difficulties to communicate and interact with people because children with autism are not capable of maintaining the social interaction and understanding the feeling of the people. In accordance with teaching and learning process, children with special needs requires extra attention in educating them in result to makes them easily understands the materials which is being teach as in SLB ( Sekolah Luar Biasa ). The role of SLB is very important because the teaching and learning processes is different in contrast with regular school. This research aims to create a game which can deliver the materials interestingly and understandable for the children with special needs. This research occurs at SLB Rumah Pintar Salatiga for 2nd grade of elementary school and this game is compatible with Books for Children with Autism in 2013 curriculum. This game contains about the simple introduction of objects within house (chair, table, TV, etc.) and number counting activity from 4 to 8. This game was made by using Unity 3D software, played with Kinect censors, DragonBone Pro for the animation, and Corel Draw X7. According to the questionaries which filled by the teacher explains that the interface of the game is very attractive, the children are more anthusiactics when playing the game based on the curriculum hence the materials within the game helps the students to understand the object within the house and helps the teacher to deliver the materials attractively.